A 10Be Moraine Chronology of the Last Glaciation and Termination at 49°N in the Mongolian Altai of Central Asia. Issue 5 (28th April 2022) - Strand, Peter D.; Putnam, Aaron E.; Sambuu, Oyungerel; Putnam, David E.; Denton, George H.; Schaefer, Joerg M.; Radue, Mariah J.; Dorj, Ariunsanaa; Amarsaikhan, Pagamsuren; Stevens, Jessica; Cole, Daniel G.
Abstract: Determining what caused the global Last Glaciation and last glacial termination, despite opposing orbital summer insolation signatures between the polar hemispheres, remains a puzzle of paleoclimatology. This problem can be addressed by comparing chronologies of glaciation from different latitudes and different climatic regimes in both hemispheres. Here, we present a 10 Be surface‐exposure chronology of glacial landforms constructed during and since the local Last Glaciation in the continental environment of Central Asia in the high Mongolian Altai (49°N, 88°E). Four belts of lateral moraines document maximal phases of the former Khoton glacier at 35, 440 ± 980 years ago, 23, 430 ± 850 years ago, 20, 780 ± 610 years ago, and 19, 520 ± 550 years ago. Our chronology indicates that deglaciation from these maximal positions began as early as 18, 810 ± 510 years ago, was well underway by 17, 680 ± 510 years ago, and was nearly completed by 16, 040 ± 490 years ago. Overall, our chronology shows that glaciation in western Mongolia overlapped with the global Last Glacial Maximum and that extensive recession from glacial‐to‐interglacial limits took place early in the last glacial termination during Heinrich Stadial 1. Khoton Nuur deglaciation led the demise of large Northern Hemisphere ice sheets and increases in radiative forcing agents by several millennia. We suggest that this rapid switch in the mode of glaciation implies the involvement of an additional climatic factor that could have produced locally rapid warming and deglaciation ∼18, 800–16, 000 years ago. Plain Language Summary: Leading hypotheses for the causes of ice ages and their terminations involve important roles for ice‐sheet feedbacks and greenhouse gases in driving global glacial cycles. Mountain glacier length records afford valuable insights into past climate conditions because mountain glaciers are highly sensitive to the effects of atmospheric temperature changes. Here, we use glacial geology and surface‐exposure dating to chart the ice‐age history of a mountain glacier system located in the Mongolian Altai of Central Asia. Results from the Altai show that the ancient glacier achieved ice‐age maxima at the same time as glaciers in midlatitude Southern Alps of New Zealand on the opposite side of the world. Likewise, rapid and extensive glacier recession took place in both locations between ∼18, 000 and 16, 000 years ago—signaling an early and rapid termination of ice age conditions in these two bipolar midlatitude locations. The rapid climate warming that drove glacier retreat in western Mongolia led to the demise of the huge Northern Hemisphere ice sheets by several millennia and even outpaced the rise of atmospheric CO2 . Any solution to the ice‐age climate puzzle must account for synchrony of glacial maxima as well as coeval rapid deglaciation in Central Asia and the Southern Hemisphere. Key Points: 10 Be dating of moraines indicates at least four glacier maxima in the Mongolian Altai during the Last Glaciation The timing of Mongolian glacier maxima overlapped with the global Last Glacial Maximum Deglaciation began as early as ∼18.8 kyrs ago and interglacial conditions were achieved by ∼16.0 kyrs ago